Implementasi Manajemen Bandwidth Dengan Menggunakan Metode Load Balancing Dan Failover Pada Router Mikrotik Dan Switch Cisco (Studi Kasus: Pusat Penguatan Dan Pemberdayaan Bahasa Kemdikbud Ristek) - Hilmy Zhahir; Maulana Ardhiansyah (INFORMATIKA, 2022)
The purpose of this study is to provide a good Quality of Service for all Internet users in a network by adjusting the Bandwidth with Load Balancing and Failover Methods on Mikrotik Routers and Cisco Switches. With the proliferation of Internet applications and the need for bandwidth to support work, the use of one ISP is currently not sufficient, so it cannot meet the needs of the Language Strengthening and Empowerment Center, for this reason it is necessary to add a new ISP link, by applying the concept of bandwidth management using load balancing and failover methods. using ISP PUSDATIN and ISP FIBERNET. The Center for Language Strengthening and Empowerment of the Language Development and Development Agency of the Ministry of Education, Culture, Research, and Technology is one of the organizational units of the Language Development and Development Agency that carries out its duties and functions in the field of strengthening and empowering the Indonesian language. In carrying out its duties and functions, the Center for Language Strengthening and Empowerment also requires internet access to support the work of its staff. Currently, the Center for Language Strengthening and Empowerment does not yet have good internet network management, such as the internet which is often disconnected and often experiences poor bandwidth constraints.